Hal "Mihya" Fa'alah? Dirasah Tajribiyyah Fi Tanmiyati al Tafkir al Naqdi Bi Adati Taqwim al Mabniyah 'Ala al A'shob - Qomariyah, Lailatul; Qodir, Abdul (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
This study aims to determine: 1) the effectiveness of "Mihya" media as a neuroscience-based evaluation tool in improving students' critical thinking skills; and 2) the difference in improving students' critical thinking skills between those who use "Mihya" media and those who do not use "Mihya." This study is a quantitative study with the quasi-experiment method with a nonequivalent control group design. Samples were taken using a purposive sampling technique. The treatment in this study was the use of "Mihya" media in the experimental group and without "Mihya" media in the control group. Learning outcome data were obtained from written tests and critical thinking ability data were obtained from closed questionnaires. This study produced several findings, namely: 1) "Mihya" media as an effective evaluation tool to improve students' critical thinking skills, and 2) there is a difference in the critical thinking skills of students who use "Mihya" media with students who do not use the media.